ANALISIS WACANA KRITIS BERITA DETIKNEWS DALAM PILKADA DKI PADA TANGGAL 13 OKTOBER 2016 - Enita Istriwati (Kantor Bahasa Provinsi Gorontalo, 2017)
In one of the 13 October 2016 news, this Detiknews media online shows certain ideology to the 2017 Jakarta Governor Election. To find out the ideology or the perspective of the media to the election, the writer analyzes the news text using critical discourse analysis theory of Norman Fairclough. Yet, the writer limits the analysis only on the description of the vocabulary, grammatical, and textual structure. The study uses a descriptive qualitative method, while the data is analyzed by using the equivalent method. The equivalent method is used to analyze the meaning of vocabulary, phrase, or sentences in the article. The data is collected by using deep-listening and note-taking techniques. The analysis result shows that Detiknews media online in “Panasnya Pilgub DKI: Ada Upaya Serius Ganjal Agus-Sylvi, Ada yang panik?” of 13 October 2016 uses vocabulary of expression to attract readers. It also uses many active sentences. As in textual structure, the text has been affected situationally, socially, and institutionally.